Transformational Leadership Membangun Energizing Collaborative Menuju Peningkatan Kinerja Organisasi Koperasi BMT Kota Semarang - Hesti Ristanto; Hani Krisnawati; Chasna Azzaki (Pusat Riset dan Inovasi Nasional, 2025)
The specific objective of this study is to identify the dominant transformational leadership style applied by the management of Koperasi BMT Kota Semarang and to provide recommendations for implementing transformational leadership to improve organizational performance through strengthened leadership and collaboration. This research employs a qualitative approach using a case study method. Data were collected through a literature review (examining theories of transformational leadership and its impact on organizational performance), interviews with leaders and team members to gain insights into the implementation of transformational leadership within Koperasi BMT Kota Semarang, and case studies of organizations that have successfully implemented transformational and collaborative leadership to illustrate best practices and their positive impacts. The targeted outcomes include improved effectiveness and efficiency in operations, leaders of Koperasi BMT Kota Semarang being able to inspire and motivate employees and members to achieve the organization’s vision, the establishment of an energetic and synergistic collaborative work culture, improved member welfare, as well as publication and dissemination of research findings to stakeholders. This study is expected to provide a clear overview of how transformational leadership can build a more energetic and collaborative team while driving overall organizational performance improvement.